2020
DOI: 10.1109/access.2020.3044025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Winding Configuration on Six-Phase Induction Machine Parameters and Performance

Abstract: Six-phase induction machines have mostly shown promise in high-power electric drive applications as well as wind energy conversion systems. Different winding configurations for six-phase stators have been published, namely, dual three-phase (D3P), symmetrical six-phase (S6P), and asymmetrical six-phase (A6P) winding layouts. Although a body of research investigating six-phase machines and their control for different six-phase winding arrangements exists, a thorough comparative study between these different arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 25 publications
0
65
0
Order By: Relevance
“…Although it has been shown in [13] that the winding layout will affect the equivalent parameters of the sequence circuits, the sequence circuits shown in Fig. 2 will be the same for all winding configurations.…”
Section: This Section Discusses the Modelling Of Six-phase Machines Based On Classical Voltage Space Decomposition (Vsd)mentioning
confidence: 97%
See 4 more Smart Citations
“…Although it has been shown in [13] that the winding layout will affect the equivalent parameters of the sequence circuits, the sequence circuits shown in Fig. 2 will be the same for all winding configurations.…”
Section: This Section Discusses the Modelling Of Six-phase Machines Based On Classical Voltage Space Decomposition (Vsd)mentioning
confidence: 97%
“…This recommended chorded winding design is commonly employed in practical six-phase stators. The terminals of the 12 phases are externally reconfigured to form any of the three six-phase winding configurations, as detailed in [13]. The study showed the following interesting conclusions:…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations